Kesiapan Mengajar Pendidikan Agama Kristen Berdasarkan Kurikulum 2013 pada Mahasiswa Sekolah Tinggi Teologi - Tunggul Yulianto; Binsar Hutasoit (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2020)
The students of the study program of PAK are prepared to become instructors at all levels of education at the elementary, junior, and senior high school levels. However, data is needed about the readiness of students in teaching at all levels. The range of levels from primary education or even PAUD and Kindergarten to junior high and high school levels is a very wide range. In this case, it is necessary to know which level is the choice of students to be ready to teach. Students have reasons for readiness and unpreparedness in teaching. Data is obtained, that all students are ready to teach elementary level for all teaching material. At the junior secondary level, teaching readiness decreases in line with the increasing difficulty of teaching materials on certain themes. At the high school level, students have the lowest teaching readiness because there are teaching materials that are more difficult than the level of education below. The results of the analysis found that the difficulty of teaching materials based on the 2013 curriculum in students is closely related to the learning process in tertiary institutions in terms of the types of subjects and special courses of PAK based on the 2013 curriculum. AbstrakMahasiswa prodi PAK disiapkan utuk menjadi pengajar pada semua jenjang pendidikan baik di tingkat pendidikan dasar, menengah pertama maupun menengah atas. Namun diperlukan data tentang kesiapan mahasiswa dalam mengajar pada semua jenjang tersebut. Rentang jenjang dari pendidikan dasar atau bahkan PAUD dan TK sampai dengan jenjang SMP dan SMA merupakan rentang yang sangat luas. Dalam hal ini perlu untuk diketahui pada jenjang manakah yang menjadi pilihan mahasiswa untuk siap megajar. Mahasiswa memiliki alasan-alasan tentang kesiapan dan ketidaksiapan dalam mengajar. Diperoleh data, bahwa semua mahasiswa sudah siap mengajar tingkat SD untuk semua materi ajar. Pada tingkat SMP, kesiapan mengajarnya menurun sejalan dengan meningkatnya kesulitan bahan ajar pada tema-tema tertentu. Pada tingkat SMA, mahasiswa memiliki kesiapan mengajar yang paling rendah karena adanya bahan ajar yang lebih sulit dibandingkan jenjang pendidikan dibawahnya. Hasil analisis didapat bahwa kesulitan bahan ajar berdasar kurikulum 2013 pada mahasiswa sangat berkaitan dengan proses belajarnya di perguruan tinggi dalam hal jenis mata kuliah dan mata kuliah khusus PAK yang berdasarkan kurikulum 2013.